Influence of Process Parameters on the Deformation of Copper Foils in Flexible-Pad Laser Shock Forming - Nagarajan, Balasubramanian; Castagne, Sylvie; Wang, Zhongke (8th International Conference on MicroManufacturing (ICOMM 2013), 2013)
This paper investigates a new microforming technique, Flexible-Pad Laser Shock Forming (FPLSF), to produce mi-crofeatures on metallic foils without rigid punches and dies. FPLSF uses the laser-induced shock pressure and a flexi-ble-pad to plastically deform metal foils into hemispherical microcraters. In order to understand the deformation characteristics of metal foils in FPLSF, it is necessary to analyze the influence of process parameters on the foil deformation. In this paper, the effects of parameters such as the flexible-pad thickness, confinement layer medium, confinement layer thickness and the number of laser pulses on the depth, diameter and shape of the craters formed on copper foils were investigated. It is found that the flexible-pad thickness should be greater than its threshold value to maximize the deformation of foils. By comparing two different confinement media, namely water and glass, it is observed that hemispherical craters were formed on the copper foils at different laser fluence values tested when using water as the confinement; whereas shockwave ripples were formed on the copper foil at higher laser fluence while using the glass confinement. Using water as confinement medium, an increase in confinement thickness from 4 mm to 7 mm resulted in 48% increase of the crater depth at 7.3 J/cm2. However, at 13.6 J/cm2, reduction in crater depth was observed for thickness greater than 6 mm after an initial increasing trend. Regarding the number of pulses, it is found that increasing the number of pulses from 1 to 3 resulted only in a small increase (less than 1%) in crater depth at 7.3 J/cm2 and 13.6 J/cm2 laser fluence whereas 19.3% increase in depth was observed at larger laser fluence (20.9 J/cm2). It is also observed that the optimum number of pulses to achieve maximum deformation is varying with the laser fluence.
Keywords: laser shock forming; ablative overlay; confinement layer; laser-induced shock pressure; Microforming